2009
DOI: 10.3122/jabfm.2009.06.090035
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Group A Streptococci in Acute Pharyngitis

Abstract: Background:The role of non-group A streptococci (non-GAS) as pathogens of acute pharyngitis is controversial. Data are limited and conflicting on whether these bacteria are true pathogens of pharyngitis and whether treatment is indicated in all cases or just select cases. However, non-GAS are well-documented as being pathogens of other diseases, including neonatal sepsis, pneumonia, endocarditis, and urinary tract infections. If non-GAS are pathogens of acute pharyngitis, treatment may speed recovery as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 12 publications
0
30
0
4
Order By: Relevance
“…suggested that Lancefield groups C and G presentations were similar to group A; 11 supported by Tiemstra et al 3 Conversely a substantial study concluded that clinical presentations were different. 16 Thus both the relevance of C and G streptococci in symptomatic presentation and the clinical predictors require clarification.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…suggested that Lancefield groups C and G presentations were similar to group A; 11 supported by Tiemstra et al 3 Conversely a substantial study concluded that clinical presentations were different. 16 Thus both the relevance of C and G streptococci in symptomatic presentation and the clinical predictors require clarification.…”
Section: Resultsmentioning
confidence: 55%
“…This supports those studies which observed similar symptomatic presentation. 11,3 If group C and G streptococci are clinically important, then rapid streptococcal antigen tests (which are targeted at group A beta-haemolytic streptococci only) will miss a significant proportion of streptococcal infection.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Such a model could potentially be used with computerised practices to document more precisely risk of streptococcal infection (Appendix 4). Although for non-group A streptococci to date we assumed Lancefield groups B and D and also Pneumococcus were not to be counted as significant pharyngeal pathogens ( Tables 2 and 3 and Appendix 4), given the ongoing debates about this issue, 13 we also present the multivariate analysis when these streptococci are included as potentially significant pathogens (see legends to Tables 2 and 3). Given the higher asymptomatic carriage rates of streptococci in children, we did not include age in the final multivariate models.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Investigating sore throat infections with highly specific RADTs will result in cases of group C and G infections being undiagnosed and untreated. The significance and clinical relevance of this issue will be investigated further in the diagnostic studies (see Chapters 2 and 3).…”
Section: Evaluation Of Five Rapid Antigen Detection Testsmentioning
confidence: 99%
See 1 more Smart Citation